Dual Exchange Markets Under Incomplete Separation : An Optimizing Model. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper constructs and analyzes an optimizing model of dual exchange markets which are incompletely separated owing to the presence of fraudulent cross transactions. The model is used to examine the implications of certain shocks, including devaluation. Devaluation first leads to the emergence of a spread with the financial exchange rate being relatively appreciated vis-a-vis the commercial rate. Over time, the financial rate depreciates beyond the level of the commercial rate. In the final phase of adjustment, the spread declines continuously until a zero spread is restored.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet